The analysis of influence of uncertainty factors on mathematical modeling of the process of reverse expansion of ammonia in low-speed reciprocating compressor stage. Part 2 - D. Kh. Sadvakasov; G. I. Chernov; V. L. Yusha (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
The paper presents the analysis of influence of the method of calculating the heat transfer coefficient on mathematical modeling of the process of reverse expansion of ammonia in the working chamber of the reciprocating compressor stage (in the area of wet steam). Alternative variants of film and drip schematization of the heat exchange process are considered. The mathematical model is based on the equations of the first law of thermodynamics for a body of variable mass, the equation of state of a real gas, the Clapeyron–Clausius and Newton–Richman equations. Based on the results of the computational and parametric analysis, the applicability of known methods for calculating the heat transfer coefficient to the object under consideration is evaluated.